Risk premia and the social cost of carbon: A review - Carolyn Kousky; Robert E. Kopp; Roger M. Cooke (Economics: The Open-Access, Open-Assessment E-Journal, 2011)
Abstract Reducing greenhouse gas emissions not only lowers expected damages from climate change but also reduces the risk of catastrophic impacts. However, estimates of the social cost of carbon, which measures the marginal value of carbon dioxide abatement, often do not capture this risk reduction benefit. Risk-averse individuals are willing to pay a risk premium, an additional amount beyond the difference in expected damages, to reduce risks. The authors review methods used and estimates obtained for calculating a risk premium to be included in the social cost of carbon. While more research is needed in this area, work to date suggests a positive, and potentially substantial, risk premium on the social cost of carbon is warranted.
Keywords: Q54; 330; climate change; social cost of carbon; risk premium; Kohlendioxid; Klimaveränderung; Soziale Kosten; Risikoprämie; Wissenschaftliche Methode; Naturkatastrophe; Klimaschutz